STRATEGIC INTEGRATION AND OPERATIONAL ANALYSIS OF UNMANNED AERIAL VEHICLE (UAV) SYSTEMS IN THE BORDER DEFENSE ARCHITECTURE OF THE ISLAMIC REPUBLIC OF IRAN (Eureka Journal of Computing Science & Digital Innovation, 2026)
This article provides a scientific analysis of the role of Unmanned Aerial Vehicle (UAV) systems in protecting the state borders of the Islamic Republic of Iran. The study examines the ISR (Intelligence, Surveillance, and Reconnaissance) and strike capabilities of UAV systems within the context of Iran's diverse geographical landscape, including mountainous, desert, and maritime regions. Furthermore, the article highlights the integration of UAVs, networked sensors, and Electronic Warfare (EW) assets within the “Smart Border” framework, alongside operational models designed to counter asymmetric threats.
Keywords: UAV, ISR systems, border security, asymmetric warfare, Mohajer-6, Shahed-129, network-centric control, A2/AD zone.